Between tension and trauma: communication's role in conflict-ridden families and separation inability - Wibowo, Deworo Putra; Rizkiana, Rina Elsa (Geuthèë Institute, Aceh, 2025)
Prolonged unresolved tension within a family can result in dysfunctional communication and pose serious risks to children’s psychological well-being. This issue becomes more complex in households where the wife acts as the primary breadwinner while the husband loses his economic role, yet the couple remains together due to social, economic, or parenting considerations. Although many studies have examined the impact of family conflict on children, few specifically address communication dynamics within families who remain in long-term conflict without the willingness or ability to separate. This study aims to analyze the interpersonal communication between husband, wife, and child in such families, and its emotional consequences for the child. Using a descriptive qualitative approach, data were collected through in-depth interviews with three families matching these criteria. The results indicate that spousal communication tends to be defensive and blame-oriented, while children exhibit emotional withdrawal, anxiety, and difficulty articulating their feelings. The findings are analyzed through Family Systems Theory, Family Maintenance Theory, and Supportive Communication Theory. Therefore, it can be concluded that role-based communication strategies and emotional validation are essential for healing processes in families that remain intact despite ongoing conflict.